Can Compensation Prevent Impoverishment? Reforming Resettlement through Investments and Benefit-Sharing Edited by Michael M. Cernea & Hari Mohan Mathur - Messerschmidt, Don (Hydro Nepal: Journal of Water, Energy and Environment, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Hydro Nepal: Journal of Water, Energy and Environment Issue No. 3, January, 2008 Page 55-56